PENGARUH KECERDASAN EMOSIONAL DAN MOTIVASI TERHADAP KINERJA PENYULUH DI DINAS PERTANIAN KABUPATEN TANGGAMUS - Anna Gustina Zainal; Amiruddin Saleh (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
The most forward elements of the bureaucracy, dealing directly with farmers and spearheading the development of agriculture is the agricultural extension. Its presence is very important in determining the success of development activities of farmers. The purpose of this study to (1) determine the effect of emotional intelligence and motivational variables on the performance of agricultural extension; (2). determine the effect of emotional intelligence and motivation variable partially on the performance of agricultural extension (3). proving variables emotional intelligence has a dominant influence compared to the performance of agricultural extension motivation. The research is a kind of survey of the Department of Agriculture agricultural extension Tanggamus. The analysis technique used: multiple regression analysis to determine the effect of the independent variable (X) studied both together and partially to the dependent variable (Y). As for the multiple linear regression model should qualify the common assumptions of regression to test heteroscedasticity, autocorrelation and multicollinearity. Based on the analysis of F test proved that the independent variable in the form of emotional intelligence(X1),motivation (X2)has a significant influence on the performance variable (Y) so that the first hypothesis is accepted. While based on t test results proved that the X variable partially significant influence to variable Y so that the second hypothesis is accepted. The dominant independent variables affect the performance is not a variable motivational variables emotional intelligence so that the third hypothesis is rejected.